HIGH LEVEL THINKING SKILLS EMPOWER STUDENTS PRIMARY EDUCATION THROUGH INNOVATIVE LEARNING - Sajidan Sajidan; Afandi Afandi (Universitas Sebelas Maret, 2018)
To reach the stage of cognitive development is higher, one form of mental ability is a very important training to students early is high level thinking skills. If it refers to the characteristics of basic education age psychology then true learning takes place must always pay attention to these aspects in accordance with the level of mental development of the child at that age. The use of models of innovative learning such as inquiry, CLIS, and learning in the TAAC can empower high level thinking skills.